msl2 mRNA is bound by free nuclear MSL complex in Drosophila melanogaster - Johansson, Anna-Mia (Oxford University Press, 2011)
In Drosophila, the global increase in transcription from the male X chromosome to compensate for its monosomy is mediated by the male-specific lethal (MSL) complex consisting of five proteins and two non-coding RNAs, roX1 and roX2. After an initial sequence-dependent recognition by the MSL complex of 150–300 high affinity sites, the spread to the majority of the X-linked genes depends on local MSL-complex concentration and active transcription. We have explored whether any additional RNA species are associated with the MSL complex. No additional roX RNA species were found, but a strong association was found between a spliced and poly-adenylated msl2 RNA and the MSL complex. Based on our results, we propose a model in which a non-chromatin-associated partial or complete MSL-complex titrates newly transcribed msl2 mRNA and thus regulates the amount of available MSL complex by feedback. This represents a novel mechanism in chromatin structure regulation.